A One‐Pot Synthesis of Hydrogen and Carbon Fuels from Water and Carbon Dioxide. Issue 7 (23rd December 2014) - Li, Fang‐Fang; Liu, Shuzhi; Cui, Baochen; Lau, Jason; Stuart, Jessica; Wang, Baohui; Licht, Stuart
<x xml:space="preserve">Abstract</x> A single‐pot electrolytic synthesis of hydrogen and carbon fuels is achieved through the use of a mixed, hydroxide/carbonate electrolyte, nickel anode (generating O2), and nickel or steel cathode (generating graphite and hydrogen). Low hydroxide fractions in the electrolyte ensure efficient carbon formation, while high fractions form only H2 at the cathode; added barium and lithium salts ensure effective nickel anode stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>